Four-country meeting on residency in France, Germany, The Netherlands and UK: 4 countries, 4 ways - Schott, Sarah; Yaribakht, Shaghayegh; Adams, Ted; van der Avoort, Irene (Archives of gynecology and obstetrics, 2014)
The 2013 "4 countries meeting" of the British, Dutch, French, and German Societies of Gynaecology and Obstetrics (RCOG, NVOG, CNGOF, DGGG) was dedicated to "Residency and clinical guidelines". The meeting was convened to compare how residency is organised in each country and to see how the political and social issues affect how residency is organised. At the same meeting we discussed the production of clinical guidelines and their importance within Europe. This report focuses on "residency" and looks at the underlying structural differences in each country. We discuss the differences and how we might learn from each other's strengths.
Gesehen am 05.02.2021